Pengembangan Modul Berbasis Model Pembelajaran Problem Solving Materi Rekonsiliasi Bank di SMK Negeri 2 Singkawang - Warneri Warneri; Iwan Ramadhan (Ideas Publishing, 2023)
This study aims to determine the results of the development of the problem solving model learning module on Bank Reconciliation material in the Financial Accounting subject for students majoring in financial and institutional accounting in bank reconciliation learning. The method used is qualitative descriptive approach. The problem in this study is that the learning design is still classic and does not adapt to the needs of students and without utilizing learning resources around the school that are sufficiently supportive of bank reconciliation material. Not optimal learning modules affect the implementation of student learning. The results of module development research based on learning models in modules have been consistent and harmonious in their design and implementation and are interesting and easy to understand.